2011
DOI: 10.1242/jeb.050997
|View full text |Cite
|
Sign up to set email alerts
|

The hydrodynamic disturbances of two species of krill: implications for aggregation structure

Abstract: Swimming capacity is dependent on size (Johnson and Tarling, 2008) and organism size is directly related to the spatial extent of the hydrodynamic disturbance, which potentially provides a sensory field for prey, predators and conspecifics (Abrahamsen et al., 2010 Accepted 15 February 2011 SUMMARY Krill aggregations vary in size, krill density and uniformity depending on the species of krill. These aggregations may be structured to allow individuals to sense the hydrodynamic cues of neighboring krill or to avo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 40 publications
(85 reference statements)
3
74
1
Order By: Relevance
“…The conflicting conclusions from these studies illustrate the variability and challenges faced when characterizing biogenic mixing. It is clear that schools of swimming animals create measurable changes in fluid disturbances, and recent laboratory studies of schooling krill confirm this (Catton et al, 2011). However, in terms of generating mixing by disrupting stratification in the ocean, vertical migration behavior may result in more effective mixing than mostly horizontally swimming animals.…”
Section: Mixing Via Biogenic Turbulencementioning
confidence: 97%
“…The conflicting conclusions from these studies illustrate the variability and challenges faced when characterizing biogenic mixing. It is clear that schools of swimming animals create measurable changes in fluid disturbances, and recent laboratory studies of schooling krill confirm this (Catton et al, 2011). However, in terms of generating mixing by disrupting stratification in the ocean, vertical migration behavior may result in more effective mixing than mostly horizontally swimming animals.…”
Section: Mixing Via Biogenic Turbulencementioning
confidence: 97%
“…This anisotropic turbulence may be caused by the anisotropic swimming pattern produced by the feeding school. Catton et al (2011) conducted a small tank experiment to study fluid motion around swimming krill using laser sheet illumination. They reported that krill ag gregations actively transferred water parcels down to successive group members, consequently disturbing the water column at a scale of aggregations.…”
Section: Spectrum Shapesmentioning
confidence: 99%
“…Although these characteristics appear to be critical for determining the intensity of the induced turbulence (Huntley & Zhou 2004), the previous observations did not consider swimming behavior but used acoustic backscatter merely to estimate population density. However, in a tank experiment, Catton et al (2011) reported that individual (not aggregated) krill were able to transfer a water parcel by a distance of 1 body length, while aggregated krill actively transferred water parcels down to successive group members and disturbed the water column at a scale of aggregations. They suggested that different biological characteristics (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…and even fish schools. With its capability to identify and track multiple organisms and measure complex flow variations in a volumetric domain, this technique can provide measurement means for researchers interested in biogenic mixing (Katija and Dabiri, 2009), in situ characterization of organisms and flow (Sutherland et al, 2011), krill schooling (Catton et al, 2011), plankton aggregation in oceanic thin layers (Durham and Stocker, 2012) or predator-prey interactions (Buskey et al, 2002;Adhikari, 2013;Rothschild and Osborn, 1988). Thus, the application of this technique can extend from investigating organism movement within benthic boundary layers to even wind-driven seed dispersal in terrestrial systems.…”
Section: Appendix 2 Extensions and Applications Of Infrared Tomographmentioning
confidence: 99%